PENGARUH STRUKTUR MODAL, BIAYA EKUITAS, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA BADAN USAHA MILIK NEGARA (BUMN) YANG TERDAFTAR DI BURSA EFEK INDONESIA - Supit, Hendry Victory; Karamoy, Herman; Morasa, Jenny (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2015)
Source of corporate funding is essential to the operations of a firm. The problem that often arises is how companies choose the capital structure that could maximise the firm value but still pay attention to the wishes of investors and creditors to take advantage of the provision of funds through equity capital and debt capital. The purpose of this paper is to examine the impact of capital structure, cost of equity, and dividend policy on the firm value at State Owned Enterprises (BUMN) that are listed in the Indonesia Stock Exchange. The population in this study are all state-owned enterprises listed on the Indonesia Stock Exchange with a study period of 2009 to 2014, totaling 20 companies. Samples were selected using purposive sampling method amounted to 13 companies. The analytical method used multiple linear regression analysis and will be processed first with using classic assumption test. As for the processing of research data using SPSS version 23.0. The test results simultaneously (F test) the capital structure, the cost of equity, and dividend policy have impact on the firm value of state-owned companies in Indonesia. After the partial test (t test), capital structure has negative impact on the firm value, but the cost of equity and dividend policy concluded no impact on firm value.